The impact of organizational growth on employees' personal initiative and commitment - Jill Walters Glombik (Journal of Applied Leadership and Management, 2020)
Research questions: The purpose of this paper is to examine the relationship between organizational growth and employees' level of personal initiative and commitment considering perceived organizational support as a mediator. The main research question is:How does rapid organizational growth affect employees' personal initiative and commitment? Methods: Empirical study at one German organization using four external surveys from 2012-2018 as well as two internal department specific surveys implemented within a year to assess the level of personal initiative and commitment among leaders and non-leaders over time. Results: The analysis showed that there was no significant difference in levels of commitment between employees in a leadership or non-leadership role. There was no evidence to prove there is a decrease in perceived organizational support and consequently commitment due to strong organizational growth. The examination of commitment with respect to job tenure revealed that commitment seems to decrease during a tenure of 5-10 years with an upward slope between 11-15 years. Regarding personal initiative, leader behaviors and attitudes influence non-leader behaviors and attitudes.
Keywords: 650